A multi-analyte immunoassay for thyroid related analytes. Issue 3 (4th May 2017) - Jain, Bharti; Kumarasamy, J.; Gholve, C.; Kulkarni, Savita; Rajan, M. G. R.
ABSTRACT: We describe the development and validation of multianalyte immunoassays (MAIA) for three analytes, viz., thyroxine (T4), thyroid stimulating hormone (TSH), and thyroglobulin (Tg) essential for assessment of thyroid function but having widely varying molecular weights. Using polycarbonate (PC) track-etched membranes (TEM) as an immobilization support and 125 I as the tracer, both competitive assay for T4 and non-competitive assay for TSH and Tg were performed on the same TEM. MAIA was found to be highly sensitive and precise with clinically useful working range and correlated very well with individual analyte immunoassays. While we have demonstrated this assay format with radiotracer, it can be used with non-isotopic tracers equally well.